2017
DOI: 10.1016/j.ijcard.2017.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes for young people with screening-detected and clinically-diagnosed rheumatic heart disease in Fiji

Abstract: Young people with screening-detected RHD have worse health outcomes than screen-negative cases in Fiji. The prognosis of clinically-diagnosed RHD remains poor, with very high mortality and complication rates. Further studies in other settings will inform RHD screening policy. Comprehensive control strategies are required for disease prevention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 21 publications
(15 reference statements)
0
12
0
2
Order By: Relevance
“…More than 80% of young initial RHD patients had not been previously hospitalized for ARF, which indicates that many ARF patients do not come to clinical attention and miss prophylactic treatment. Increasing public and clinician awareness of ARF, echocardiographic screening for high-risk children, and new diagnostic tools may improve case identification ( 21 , 40 ). If a clear prognostic benefit is demonstrated from echocardiography screening programs, this finding may strongly support the use of targeted screening among high-risk New Zealand children.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More than 80% of young initial RHD patients had not been previously hospitalized for ARF, which indicates that many ARF patients do not come to clinical attention and miss prophylactic treatment. Increasing public and clinician awareness of ARF, echocardiographic screening for high-risk children, and new diagnostic tools may improve case identification ( 21 , 40 ). If a clear prognostic benefit is demonstrated from echocardiography screening programs, this finding may strongly support the use of targeted screening among high-risk New Zealand children.…”
Section: Discussionmentioning
confidence: 99%
“…Without prophylaxis, some patients may experience further cardiac damage eventually resulting in clinically evident RHD. Therefore, echocardiographic screening of high-risk children to identify subclinical RHD cases and provide prophylactic treatment/monitoring may be needed to effectively reduce the RHD burden ( 20 , 21 ).…”
mentioning
confidence: 99%
“…Given the devastating complications and high mortality rate of clinically diagnosed RHD, [44] screening may identify patients who are likely to benefit from cardiac surgery prior to the development of irreversible heart failure, infective endocarditis or stroke. [45] While surgical intervention or prophylactic penicillin may not always be necessary, close follow up may be warranted, especially in patients in groups shown to have a greater propensity for progression. Although we were unable to perform a meta-regression, predictors for progression were extremely heterogeneous and some studies did not find any significant…”
Section: Plos Onementioning
confidence: 99%
“…Furthermore, in most of the included studies, even in lesions that progress, there were extremely low rates of heart failure, severe valvular disease and death Latent definite RHD was shown to have a high complication rate (20% over a median follow-up of 7 years) in another cohort but this was postulated to be a country specific finding and may have represented a high rate of "missed clinical disease". [45] In low risk groups, the value of screening may be small, therefore like all tests, echocardiographic screening for the purpose of prophylactic penicillin administration needs to be evaluated in the context of pre-test probability. A randomised trial is the ideal way to solve this conundrum and must demonstrate feasibility, cost effectiveness and an incremental value of screening prior to its widespread implementation.…”
Section: Plos Onementioning
confidence: 99%
“…[ 26 ] Although there is a paucity of data regarding outcomes of these patients, recent evidence suggests that screening-detected RHD can progress significantly within 4–5 years with clinically-diagnosed RHD progressing the most rapidly. [ 27 28 29 ] Some screening-detected RHD cases have progressed to require valve surgery,[ 28 ] yet other studies have demonstrated a more stable course with over 90% of patients remaining only mildly affected. [ 29 30 ] Given that subclinical RHD was excluded from the GBD estimates, it is likely, therefore, that the study underestimates the true burden of disease, at least to some degree.…”
Section: Identifying Core Challenges In the Prevention And Control Ofmentioning
confidence: 99%